Investigation of the functional expression of purine and pyrimidine receptors in porcine isolated pancreatic arteries - Alsaqati, M.; Chan, S.L.F.; Ralevic, Vera (Springer Verlag, 2014)
Receptors for purines and pyrimidines are expressed throughout the cardiovascular system. This study investigated their functional expression in porcine isolated pancreatic arteries. Pancreatic arteries (endothelium intact or denuded) were prepared for isometric tension recording and preconstricted with U46619, a thromboxane A2 mimetic; adenosine-5′-diphosphate (ADP), uridine-5′-triphosphate (UTP) and MRS2768, a selective P2Y2 agonist, were applied cumulatively, while adenosine-5′-triphosphate (ATP) and αβ-methylene-ATP (αβ-meATP) response curves were generated from single concentrations per tissue segment. Antagonists/enzyme inhibitors were applied prior to U46619 addition. ATP, αβ-meATP, UTP and MRS2768 induced vasoconstriction, with a potency order of αβ-meATP > MRS2768 > ATP ≥ UTP. Contractions to ATP and αβ-meATP were blocked by NF449, a selective P2X1 receptor antagonist. The contraction induced by ATP, but not UTP, was followed by vasorelaxation. Endothelium removal and DUP 697, a cyclooxygenase-2 inhibitor, had no significant effect on contraction to ATP but attenuated that to UTP, indicating actions at distinct receptors. MRS2578, a selective P2Y6 receptor antagonist, had no effect on contractions to UTP. ADP induced endothelium-dependent vasorelaxation which was inhibited by MRS2179, a selective P2Y1 receptor antagonist, or SCH58261, a selective adenosine A2A receptor antagonist. The contractions to ATP and αβ-meATP were attributed to actions at P2X1 receptors on the vascular smooth muscle, whereas it was shown for the first time that UTP induced an endothelium-dependent vasoconstriction which may involve P2Y2 and/or P2Y4 receptors. The relaxation induced by ADP is mediated by P2Y1 and A2A adenosine receptors. Porcine pancreatic arteries appear to lack vasorelaxant P2Y2 and P2Y4 receptors.